Photoelectrochemical etching and dye sensitization of Bridgman grown single crystal SnS2 photoanodes - Sharp, Laura Inman, author; Parkinson, Bruce, advisor; Lee, Robert E., committee member; Levinger, Nancy, committee member (Colorado State University. Libraries, 2002)
The growth of n-type single crystal SnS2 with various carrier concentrations and different dopant elements has been accomplished. The electronic properties of these crystals were determined through Hall and Mott-Schottky measurements. These measurements showed that the carrier concentration was uniform throughout the middle section of the crystals. Analysis of the photocurrent data revealed that a direct correlation exists between the carrier concentration, the minority carrier concentration and the band-gap incident photon to current efficiency (IPCE).

Dye sensitization of SnS2 with methylene blue (MB+), azure B (AZB+), oxazine (OX+) and cresyl violet (CV+) has been studied. Higher dye sensitized IPCE's for MB+ and CV+ were obtained near step edges and defects on the crystal surface due to intercalation of dye molecules into exfoliated areas of the crystal. Langmuir analysis of the MB+ adsorption data on a smooth surface indicated that the dye molecules were lying flat on the surface. Photoxidation studies with MB+ and CV+ showed that these dyes exhibited both different excited state properties and distinct adsorption behavior with CV+ displaying significantly faster rates of adsorption and desorption. Analysis of the MB+, AZB+, CV+ and OX+ IPCE's showed that the IPCE values for these dyes were unaffected by the SnS2 carrier concentration. Impedance measurements and quantum measurements from both photoaction spectra and photocurrent-voltage curves indicated that recombination appeared to influence the dye sensitization process. The identity of the recombination centers was probed by thiol addition and annealing SnS2 crystals in S vapor to change the S content of the surface.

Photoelectrochemical (PEC) studies showed that an increased IPCE was associated with roughening the SnS2 surface. An optimum degree of PEC etching for SnS2 electrodes was observed in regards to the dye sensitized IPCE, the band gap IPCE and their ratio. The relationship between the MB+ sensitized IPCE and the extent of photoetching showed a dependence on the SnS2 carrier concentration. Analysis of the MB+ adsorption isotherm showed that PEC etching also appeared to influence the binding strength of the dye as the heat of adsorption was slightly greater for MB+ on photoetched versus unetched SnS2.
Keywords: analytical chemistry